2022
DOI: 10.53909/rms.04.02.0195
|View full text |Cite
|
Sign up to set email alerts
|

Closed Loop Supply Chain: Evaluating Ecological Footprint

Abstract: Purpose:  The purpose of this research is to evaluate the success of the closed-loop E-waste supply chain operations, primarily focused on achieving sustainability objectives related to the manufacturing, distribution, reusing, and discarding of electrical components. Methodology: The supply chain operations reference model offers suggestions and benchmarking tools to monitor the performance of supply chains and enhance the processes. This study illustrates a conceptual framework to show how these standards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Hung (2020) examined that the time and frequency are not connected between oil markets and stock markets in Hungry, by using econometric models like DCC-GARCH and wavelet coherence analysis. Their results revealed that the higher correlations between Budapest stock market and crude oil prices (Khaskhelly et al, 2022). It was confirmed that commodity markets like crude oil have significant impact on stock market of Hungry in short-run.…”
Section: Empirical Review 221 Stock Market and Oil Pricesmentioning
confidence: 77%
See 1 more Smart Citation
“…Hung (2020) examined that the time and frequency are not connected between oil markets and stock markets in Hungry, by using econometric models like DCC-GARCH and wavelet coherence analysis. Their results revealed that the higher correlations between Budapest stock market and crude oil prices (Khaskhelly et al, 2022). It was confirmed that commodity markets like crude oil have significant impact on stock market of Hungry in short-run.…”
Section: Empirical Review 221 Stock Market and Oil Pricesmentioning
confidence: 77%
“…Since few years, Pakistan has been dealing with a number of basic risk variables, including interest rates, inflation, rupee value, and oil prices. The Pakistani financial system has been noted as being unable to adapt to the full financial crisis (Khaskhelly et al, 2022). The stock market is significantly impacted by changes in gold prices on a global scale.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies suggest a positive correlation between sustainable edges and firm value, the alarm is that sustainable procedures are expensive, and cost does not always compensate for profits (Khaskhelly et al, 2022). There are many variables that deduce the incentive for manufacturing companies to greater involvement in SCSS.…”
Section: Customer Satisfaction and Scssmentioning
confidence: 99%
“…As public awareness of the makeup industry's lack of diversity rises, cosmetic companies will have more opportunity to offer a larger selection of hues in their products . Consumers have grown more conscious of the push to extend cosmetic shade offerings to assist the BIPOC community as there are more beauty and cosmetics brands on the market than ever before (Zeb Khaskhelly et al, 2022). As public awareness of the problem grows, beauty companies will be more likely to create a wider range of products.…”
Section: Community In the Makeup Industrymentioning
confidence: 99%